1998
DOI: 10.1364/josaa.15.000307
|View full text |Cite
|
Sign up to set email alerts
|

Color constancy in the nearly natural image 2 Achromatic loci

Abstract: Most empirical work on color constancy is based on simple laboratory models of natural viewing conditions. These typically consist of spots seen against uniform backgrounds or computer simulations of flat surfaces seen under spatially uniform illumination. In this study measurements were made under more natural viewing conditions. Observers used a projection colorimeter to adjust the appearance of a test patch until it appeared achromatic. Observers made such achromatic settings under a variety of illuminants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
180
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(199 citation statements)
references
References 42 publications
19
180
0
Order By: Relevance
“…The level of colour constancy achieved by human observers is typically less for simulated scenes than for real scenes. Brainard (1998) found that with real scenes, observers can compensate for 84% of the change in illumination (assessed via achromatic settings), while typical performance with scenes presented on computer monitors suggests only 50% compensation. Yang & Maloney (2001) took several steps to ensure that their simulated scenes were as real as possible, and their observers achieved achromatic settings that compensated for 65% of the change in illumination.…”
Section: Estimating the Illuminant (A) What Is Estimated?mentioning
confidence: 94%
See 2 more Smart Citations
“…The level of colour constancy achieved by human observers is typically less for simulated scenes than for real scenes. Brainard (1998) found that with real scenes, observers can compensate for 84% of the change in illumination (assessed via achromatic settings), while typical performance with scenes presented on computer monitors suggests only 50% compensation. Yang & Maloney (2001) took several steps to ensure that their simulated scenes were as real as possible, and their observers achieved achromatic settings that compensated for 65% of the change in illumination.…”
Section: Estimating the Illuminant (A) What Is Estimated?mentioning
confidence: 94%
“…Fairchild & Lennie 1992;Brainard 1998). Importantly for these studies, Morgan et al (2000) have shown that accuracy can be as great with an implicit as with an explicit standard.…”
Section: Cone Sensitivities S(λ) M(λ) L(λ)mentioning
confidence: 97%
See 1 more Smart Citation
“…The human visual system is, to a certain extent, colour constant [1,4,5]; that is, it discounts the colour of the illumination. This is why, for example, snow always appears white, no matter which illuminant it is observed under.…”
Section: Introductionmentioning
confidence: 99%
“…The chromatic context of the surface might bias this estimate, but it is still correlated with the colour of the illuminant. The extent of this bias can be exploited as a quantitative probe of the effects of scene structure [34,37]. If subjects compare the surface with an imaginary standard, then the task is similar to asymmetric colour matching, but is less precise [16].…”
Section: Judging Whitementioning
confidence: 99%